A novel SHANK3 interstitial microdeletion in a family with intellectual disability and brain MRI abnormalities resembling Unidentified Bright Objects. (November 2017) - Terrone, Gaetano; Vitiello, Giuseppina; Genesio, Rita; D'Amico, Alessandra; Imperati, Floriana; Ugga, Lorenzo; Giugliano, Teresa; Piluso, Giulio; Nitsch, Lucio; Brunetti-Pierri, Nicola; Del Giudice, Ennio
Abstract: Background: SHANK3 mutations are responsible for Phelan-McDermid syndrome but they are also associated with autism and/or intellectual disability. Case report: We report a family with four affected individuals including the 37 year-old mother, her 12 year-old male monozygotic twins and 8 year-old daughter harboring a novel SHANK3 interstitial microdeletion. All four members presented with intellectual disability of variable severity. The twins showed brain abnormalities similar to Unidentified Bright Objects (UBOs), typically detected in patients with Neurofibromatosis type 1 (NF1), but they did not display causative mutations in NF1 gene . Conclusion: To date, this is the first report of an affected individual with SHANK3 interstitial deletion able to reproduce. Moreover, we found a previously unreported possible association between SHANK3 deletion and UBOs-like lesions in the brain. Highlights: Mutations involving SHANK3 are responsible for Phelan-McDermid syndrome. SHANK3 mutations are described in cases of autism or intellectual disability (id). We report a family with id and brain abnormalities, due to a novel SHANK3 deletion. This is the first report of an individual, harboring SHANK3 deletion, able to reproduce. Unidentified Bright Objects-like brain lesions may be related to SHANK3 deletion.